3D Printing of Free‐Standing Stretchable Electrodes with Tunable Structure and Stretchability. Issue 11 (3rd July 2017) - Wei, Hong; Li, Kai; Liu, Wen Guang; Meng, Hong; Zhang, Pei Xin; Yan, Chao Yi
Abstract : Free‐standing stretchable electrodes with high stretchability and resistance stability are desired for future wearable electronic applications. However, it is very difficult to achieve high stretchability (typically restricted by the substrate) and meanwhile maintain low resistance change upon stretching. Innovative designs and fabrication strategies need to be developed to meet the required characteristics. We report the successful fabrication of free‐standing wavy elastic electrodes achieving very high stretchability (>300% for PDMS) and outstanding resistance stability (only 5% relative resistance change at 100% strain), simultaneously. We systematically studied designs with different joining angles and shapes to optimize the electrode performances. The 3D free‐standing electrodes with outstanding stretchability and electrical stability has great potential for further optimizations and applications in future stretchable and wearable electronic devices. Abstract : We demonstrate the successful 3D printing of wavy elastic electrodes with high stretchability and excellent resistance stability. Stretchable electrodes with different shapes and designs were systematically studied. Serpentine shaped design with 45° joining angle exhibited the best performances, which is in contrary to conventional 2D electrodes. Our fabrication strategy paves the way for further 3D printing of more complex stretchable electronic devices.